Thermal fluctuations, QNMs, and emission energy of charged ADS black hole with nonlinear electrodynamics - Javed, Faisal; Basit, Abdul; Caliskan, Aylin; Güdekli, Ertan (Frontiers in Astronomy and Space Sciences, 2023)
This paper examines the thermodynamics of charged anti-de-Sitter black hole with nonlinear electrodynamics using quasi-normal modes and thermal fluctuations. For this purpose, we calculate the Hawking temperature and discuss the stable configuration of the considered black hole using heat capacity. First, we study the interesting aspects of the emission of energy. Then, we explore the effects of thermal corrections on thermodynamical quantities as well as the corrected energies of the system. We study the phase transitions of the system in the background of thermal fluctuations. It is concluded that the presence of coupling constant enhances the thermodynamically stable configuration of uncharged and charged anti-de-Sitter black hole geometries. We highlight that our results are in good agreement with the thermodynamics of the previous black hole solutions and assumptions presented in the literature.